Design and Synthesis of Nitrogen‐Rich Azo‐Bridged Furoxanylazoles as High‐Performance Energetic Materials. Issue 59 (29th September 2021) - Larin, Alexander A.; Shaferov, Alexander V.; Kulikov, Alexander S.; Pivkina, Alla N.; Monogarov, Konstantin A.; Dmitrienko, Artem O.; Ananyev, Ivan V.; Khakimov, Dmitry V.; Fershtat, Leonid L.; Makhova, Nina N.
Abstract: A series of novel energetic materials comprising of azo‐bridged furoxanylazoles enriched with energetic functionalities was designed and synthesized. These high‐energy materials were thoroughly characterized by IR and multinuclear NMR ( 1 H, 13 C, 14 N) spectroscopy, high‐resolution mass spectrometry, elemental analysis, and differential scanning calorimetry (DSC). The molecular structures of representative amino and azo oxadiazole assemblies were additionally confirmed by single‐crystal X‐ray diffraction and X‐ray powder diffraction. A comparison of contributions of explosophoric moieties into the density of energetic materials revealed that furoxan and 1, 2, 4‐oxadiazole rings are the densest motifs while the substitution of the azide and amino fragments on the nitro and azo ones leads to an increase of the density. Azo bridged energetic materials have high nitrogen‐oxygen contents (68.8–76.9 %) and high thermal stability. The synthesized compounds exhibit good experimental densities (1.62–1.88 g cm −3 ), very high enthalpies of formation (846–1720 kJ mol −1 ), and, as a result, excellent detonation performance (detonation velocities 7.66–9.09 km s −1 and detonation pressures 25.0–37.7 GPa). From the application perspective, the detonation parameters of azo oxadiazole assemblies exceed those of the benchmark explosive RDX, while a combination of high detonation performance and acceptable friction sensitivity of azo(1, 2, 4‐triazolylfuroxan) make it a promising potential alternative to PETN. Abstract : Handle with care : A series of polyazole structures incorporating azo‐bridged heterocyclic backbones was synthesized by simple and efficient chemical routes. Structural features of the newly prepared energetic materials enabled modulation of their functional properties. Due to high densities and exceptionally high enthalpies of formation, these energetic materials showed excellent detonation performance exceeding that of benchmark explosives RDX and PETN.